MODERASI BERAGAMA DAN TEOLOGI TOLERANSI: PERAN TOKOH AGAMA DI DESA JELOK, BOYOLALI - Muallifah, Atika; Sutomo, Imam (Academic Journal of Islamic Principles and Philosophy, 2024)
Every human being must always live with tolerance toward others, as we are a religious community living in Indonesia, a country with various ethnicities, nations, races, cultures, and religions. We must uphold the teachings of our respective beliefs without disturbing or damaging the beliefs of others. This study uses a literature review method with a descriptive-analytical approach and field research in Jelok Village, Cepogo District, Boyolali Regency. Religious moderation can be concluded as practicing a religion in a balanced way. The principles of Islamic tolerance are, first, that Islamic tolerance is limited and focuses on social relationships; second, it involves allowing and creating a conducive environment for others to worship; and third, in practicing tolerance, the purity of faith and Sharia must be maintained. Jelok Village is able to maintain harmony despite having four different religions and one different belief system within the community.